Upaya Pemerintah Kabupaten Kepulauan Meranti dalam Penyediaan Air Bersih di Kecamatan Tebing Tinggi tahun 2012-2014 - Dwi Susanti; Wan Asrida (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2016)
Government which includes local government (province/city/district) is a state organs that has an authority in fulfilling its function to achieve its goals. The function of government includes arrangement, development, empowerment and services. Those functions are interrelated, especially to assest the limitation to fulfill the availability of clean water in Meranti District. This issue is already faced before the expansion of the district. The district belongs to peat area with the characteristic of dark red water in colour, thus force the local government to provide clean water from the dark red water.